Bisphenol A and alkylphenols concentrations in selected mariculture fish species from Pulau Kukup, Johor, Malaysia - Nur Afifah Hanun, Ismail; Wee, Sze Yee; Ahmad Zaharin, Aris (Pergamon-Elsevier Science LTD, 2018)
Endocrine disrupting compound (EDC) contamination in food is a global concern. Concerning potential environmental and human health exposed to EDCs via food intake, an experiment was conducted on the selected EDCs concentration in the mariculture fish, Trachinotus blochii (golden pomfret), Lutjanus campechanus (snapper), and Lates calcarifer (sea bass) at Pulau Kukup, Johor. Mariculture activity at Pulau Kukup involves active export of fishes to Singapore and Indonesia. The recovery of BPA (bisphenol A), 4OP (4-octylphenol), and 4NP (4- nonylphenol) were 61.54%–93.00%, 16.79%–17.13%, and 61.24%–71.49%, respectively. Relatively high concentration of BPA was recorded in T. blochii (0.322 ng/g), followed by L. calcarifer (0.124 ng/g) and L. campechanus (0.023 ng/g). Furthermore, 4OP and 4NP were detected only in T. blochii at concentrations of 0.084 ng/g and 0.078 ng/g, respectively. The results of the present study provide insights on monitoring and managing mariculture activity in relation to environmental protection and food safety.